Computational Study Natural Color Essence (Dyes) As Active Material On Organic Solar Cell With Density Functional Theory (DFT) - Male, Yusthinus T; Sutapa, I Wayan; Ranglalin, Olivia M. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2015)
Computational calculation has been done for anthocyanin, tocoferol and they derivatives. The computational calculation was conduct to know the compound potential of anthocyanin, tocoferol and they derivatives as active material on organic solar cell. Computational calculation was done by used Gaussian 03 for windows with ab inito alternative electron structure theory namely Density Functional Theory (DFT) with B3LYP method at basis set 6-31G (d). Computational calculation obtains that the structure of anthocyanin, tocoferol and they derivatives were symmetrical. There were two compounds of anthocyanin (A1 and A5) and two compounds of tocoferol (T3 and T4) which more stable than the others compounds. The compounds had lowest energy gap were consist of A1= 0.12629 eV, A5= 0.12570 eV, T3= 0.19334 eV and T4= 0.19231 eV. The moment dipole from compound of anthocyanin, tocoferol and they derivatives had highest value, they were A1 and T1 while the total energy had lowest value they A2 and T1. The Substituent methoxy and hydroxy were added the density load of C atom was substituted so it would increase the activity of the phenyl ring on anthocyanin and they derivatives, while substituent methyl and hydroxy were added the density load of C atom was substituted so it was increase the activity of the phenyl ring on tocoferol and they derivatives. For compounds of anthocyanin main orbital populations showed that there were load transfer only from middle chain (ether) and compounds of tocoferol main orbital populations showed that there was load transfer only from phenyl ring. The method of density functional B3LYP/6-31G(d) would be applied to structure prediction and electronic characteristic of anthocyanin, tocoferol compounds and they derivatives before synthetic.